Ceramic Materials Synthesis, Characterization, Applications and Recycling - Eliche Quesada, Dolores; Perez Villarejo, Luis; Sánchez Soto, Pedro (IntechOpen, 2019)
Scientific and technological development has led to the formulation of tailor-made materials, which have given rise to materials with new structural and industrial applications. This book aims to analyze the synthesis, characterization, and applications of ceramic materials. This includes an introduction to traditional and advanced ceramics, the use of traditional ceramic materials as ideal candidates for absorbing wastes, and the synthesis and characterization of advanced ceramics as nanoceramics, ytria ceramics, and electronic ceramics.